An Assessment of Welfare Conditions in Wildlife Markets across Morocco. Issue 3 (3rd July 2019) - Bergin, Daniel; Nijman, Vincent
ABSTRACT: The welfare of wild-caught animals in markets has generally been overlooked by both wildlife trade and welfare studies, despite the potential negative impacts on the animals. Morocco is a member of the World Organisation for Animal Health and has proposed draft legislation prohibiting mistreatment or abuse of animals in captivity. There is still, however, a bustling wild animal trade, and vendor compliance with industry-standard best practices is lacking. This study provides insight into the conditions of 2113 wild-caught animals in markets in six of the largest cities in Morocco by scoring their welfare based on four of the Farm Animal Welfare Committee Five Freedoms: freedom from hunger and thirst, freedom from discomfort, freedom to express normal behavior, and freedom from distress. Over 88% of animals were housed in situations that broke all four of the freedoms measured, and only 9 animals were in situations that broke none. Access to water, sun/heat exposure, and ability to hide from stressors were particularly poor. We urge the Moroccan government to fulfill its commitment to establish welfare laws and devote resources to their application.